Rural electrification through mini-grids: Challenges ahead - Jörg Peters; Maximiliane Sievert; Michael A. Toman (RWI - Leibniz-Institut für Wirtschaftsforschung, 2018)
Recent debates on how to provide electricity to the roughly one billion still unconnected people in developing countries have identified mini-grids as a promising way forward. High upfront costs of transmission lines are avoided, and unlike home-scale solar, mini-grids can provide sufficient electricity for productive uses. This note outlines the challenges the mini-grid sector faces to achieve that potential. To date, few examples of sustainably working mini-grid programs exist. We identify regulatory issues, low electricity demand in rural areas, high payment default rates and over-optimistic demand projections as among the key challenges. Business models that account for high transaction costs in rural areas and are based on realistic demand forecasts could considerably increase the commercial viability of village grids.
Keywords: H54; O13; O21; Q48; 330; public infrastructure; rural electrification; energy planning systems